Targeting Epigenetic Processes in Photodynamic Therapy-Induced Anticancer Immunity - Wachowska, Malgorzata; Muchowicz, Angelika; Golab, Jakub (Frontiers in Oncology, 2015)
Photodynamic therapy (PDT) of cancer is an approved therapeutic procedure that generates oxidative stress leading to cell death of tumour and stromal cells. Cell death resulting from oxidative damage to intracellular components leads to the release of damage-associated molecular patterns (DAMPs) that trigger robust inflammatory response and creates local conditions for effective sampling of tumour-associated antigens (TAA) by antigen presenting cells. The latter can trigger development of TAA-specific adaptive immune response. However, due to a number of mechanisms, including epigenetic regulation of TAA expression, tumour cells evade immune recognition. Therefore, numerous approaches are being developed to combine PDT with immunotherapies to allow development of systemic immunity. In this review we describe immunoregulatory mechanisms of epigenetic treatments that were shown to restore the expression of epigenetically silenced or down-regulated major histocompatibility complex (MHC) molecules as well as TAA. We also discuss the results of our recent studies showing that epigenetic treatments based on administration of methyltransferase inhibitors in combination with photodynamic therapy can release effective mechanisms leading to development of antitumour immunity and potentiated antitumour effects.